The non-contractual civil liability of the state in administrative acts for the portuguese legal system: tortious liability, risk liability and legal liability - Pinto Alves, Patrícia Marlene (2019)
This paper addresses the non-contractual civil liability of the State and Public Entities for the administrative functions of the Portuguese legal order. This paper discusses considerations about the varied types of liability: tortious (which comprehends illicit facts), risk liability, and liability for licit facts [because it could acknowledge Public Administration liability in situations where its practice is conducted on a licit way]. Finally, this article also mentions the relevance of Portuguese Law No. 67/December 31, 2007, together with the Constitution of the Portuguese Republic, with the Civil Code, and with the Portuguese Expropriation Code.